Reactive Oxygen Species Interact With NLRP3 Inflammasomes and Are Involved in the Inflammation of Sepsis: From Mechanism to Treatment of Progression - Zhao, Shuai; Chen, Fan; Yin, Qiliang; Wang, Dunwei; Han, Wei; Zhang, Yuan (Frontiers in Physiology, 2020)
Abstract Over the past 10 years, the crisis of sepsis has remained a great challenge. According to data from 2016, the sepsis-related mortality rate remains high. In addition, sepsis consumes extensive medical resources in intensive care units, and anti-inﬂammatory agents fail to improve sepsis-associated hyperinﬂammation and symptoms of immunosuppression. The specific immune mechanism of sepsis remains to be elucidated. Reactive oxygen species (ROS) are triggered by energy metabolism and respiratory dysfunction in sepsis, which not only causes oxidative damage to tissues and organelles, but also are known to promote apoptosis, autophagy, and alter inflammasome activation. Inhibiting the negative effects of ROS and inflammasomes therefore provides the possibility of reversing the excessive inflammation during sepsis. In this review, we describe the mechanisms of ROS and inflammasomes during sepsis, provide prevention strategies, and identify fields that need further study.